Antibacterial Activity of Crude Extract and Purified Acetogenins from Annona muricata Seeds - Gabriela Aguilar-Hernández; Brandon A. López-Romero; Alejandro Pérez-Larios; José M. Ruvalcaba-Gómez; Inkar Castellanos-Huerta; Guillermo Tellez-Isaias; Victor M. Petrone-García; Luis M. Anaya-Esparza; Efigenia Montalvo-González (Applied Sciences, 2022)
Currently, several biological activities are attributed to the acetogenins (ACGs) of Annonaceae (including Annona muricata); among these is antimicrobial activity. The main focus of this experiment was to evaluate the antimicrobial effect of the crude extract (CE) and purified acetogenins (P-ACGs) from the endosperm of A. muricata seeds using agar disk diffusion, lethality, sub-lethal, and potential damage membrane tests against Gram-positive and Gram-negative microorganisms. According to the results, P-ACGs present the highest antibacterial effect (12.5–4000 µg/mL) against Enterococcus faecalis (11–15.67 mm), Listeria monocytogenes (12–18 mm), Aeromonas hydrophila (10.33–11.67 mm), Bulkholderia cenocepacia (11–12 mm), and Salmonella paratiphy (11–15.67 mm), and a minimum inhibitory concentration ranging from 0.009 to 12.50 µg/mL. Measurement of the membrane potential shows that, in the presence of P-ACGs, the number of viable cells is reduced, with a significant logarithmic reduction observed (0.38, 1.27, and 1.81 CFU/mL) and a significant sub-lethal lesion (57.78, 96.14, and 98.42%) in Escherichia coli, E. faecalis, and L. monocytogenes, respectively. According to this study, the results demonstrate that P-ACGs from A. muricata seeds are potent and effective antibacterial compounds with potential pharmaceutical applications.